Bullying behaviors among medical sciences students in clinical settings: a cross-sectional study - Mohammadreza Dinmohammadi; Maryam Mohammadi; Lida Sasania; Mehran Tahrekhani (Mashhad University of Medical Sciences, 2024)
Background: The prevalence of bullying behaviors in clinical education environments is an important obstacle for students' learning, because it has severe psychological consequences. This study was conducted with the aim of determining the incidence of bullying behaviors among medical students in clinical education environments.Method: This cross-sectional study was conducted in 2019-2020 among medical, undergraduate nursing, midwifery, operating room technology, and anesthesiology students. The research environment consisted of selected teaching hospitals in Zanjan city, Iran, while the sampling method was stratified random sampling. Data were collected using the 18-item Bullying Behaviors in Nursing Education (BBNE) questionnaire and analyzed using SPSS software version 24.Results: Of the 391 participants, the majority (% 61.9) were women, single, with an average age of 22.88±1.71 years. The total bullying score was 16.46±13.44, which was considered low on the range of 0-90. The dimension of aggression towards the student's personality had the highest score of 7.29±6.54. A significant relationship existed between the total bullying score and age, field of study, marital status, place of residence, and semester (P<0.05).Conclusion: The findings indicated a low occurrence of bullying among medical students. Additionally, those who were married, older, and highly educated were more vulnerable to being bullied. Universities ought to improve students' capacity to recognize bullying in clinical education surroundings and instruct them on how to react.